2016
DOI: 10.1136/bmjgh-2016-000055
|View full text |Cite
|
Sign up to set email alerts
|

Trends and level of control of hypertension among adults attending an ambulatory HIV clinic in Kampala, Uganda: a retrospective study

Abstract: BackgroundWith an ageing HIV-positive population, sub-Saharan Africa is now facing a dual epidemic of communicable and non-communicable diseases (NCDs). This study aimed to assess trends in the prevalence of hypertension and factors associated with hypertension, among adults attending an ambulatory HIV clinic in Kampala, Uganda.MethodsWe conducted a retrospective chart review to identify patients with hypertension. We used a random number generator to select 400 patient charts from each year from 2009 to 2014.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 16 publications
1
34
0
Order By: Relevance
“…Hypertension is a recognised risk factor for AKI among African patients [ 9 ], although this is not a consistent finding [ 24 ]. Comorbidities, such as hypertension, are increasingly prevalent in sub-Saharan Africa [ 25 ]. There was a known history of CKD in 5.5% of patients in our study; none had a known baseline renal function result available at the time of their admission.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension is a recognised risk factor for AKI among African patients [ 9 ], although this is not a consistent finding [ 24 ]. Comorbidities, such as hypertension, are increasingly prevalent in sub-Saharan Africa [ 25 ]. There was a known history of CKD in 5.5% of patients in our study; none had a known baseline renal function result available at the time of their admission.…”
Section: Discussionmentioning
confidence: 99%
“…Execution of HTN screening and treatment is generally suboptimal since it is at the discretion of the clinician especially at the lower performing HIV clinics. Suboptimal screening leads to low levels of awareness, treatment, retention and control of HTN among PLHIV [7][8][9][10][11][12]18].…”
Section: Discussionmentioning
confidence: 99%
“…Previous cohort studies in SSA have shown that about 21% of PLWH were hypertensive, 22% had hypercholesterolaemia and 3% were diabetic [4,5]. These high levels of risk factors increase the likelihood of cardiovascular diseases (CVD) such as stroke and ischaemic heart disease (IHD), jointly, and together with the likely direct effect of HIV infection on CVD outcomes [5][6][7][8]. Concomitantly, improved viral suppression and life expectancy among PLWH stemming from expanded access to antiretroviral therapy (ART), now offer a greater time window for NCDs to develop to full manifestation as PLWH are ageing [9].…”
Section: Introductionmentioning
confidence: 99%